2021
DOI: 10.5121/ijma.2021.13403
|View full text |Cite
|
Sign up to set email alerts
|

Audio Cryptography via Enhanced Genetic Algorithm

Abstract: As communication technologies surged recently, the secrecy of shared information between communication parts has gained tremendous attention. Many Cryptographic techniques have been proposed/implemented to secure multimedia data and to allay public fears during communication. This paper expands the scope of audio data security via an enhanced genetic algorithm. Here, each individual (audio sample) is genetically engineered to produce new individuals. The enciphering process of the proposed technology acquires,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Salamudeen et al [ 27 ] proposed an enhancement to Audio Cryptosystems by applying GA. Each initial audio sample is genetically engineered by applying several operators to yield the final cipher audio. Garg et al [ 28 ] suggested a genetic algorithm and DNA cryptography-based encryption scheme for Fog Networks.…”
Section: Related Workmentioning
confidence: 99%
“…Salamudeen et al [ 27 ] proposed an enhancement to Audio Cryptosystems by applying GA. Each initial audio sample is genetically engineered by applying several operators to yield the final cipher audio. Garg et al [ 28 ] suggested a genetic algorithm and DNA cryptography-based encryption scheme for Fog Networks.…”
Section: Related Workmentioning
confidence: 99%